Kandungan Informasi Pelaporan Kerugian dan Hubungan dengan Pergerakan Return Saham (Studi Empiris pada Bursa Efek Jakarta) - Veno Ajie (The Indonesian Journal of Accounting Research, 2013)
This study investigates the information content of losses reported by companies to investors. It was motivated by the possibility that losses and profits have different associations with share return because losses are perceived by investors as temporary. Losses are likely to be considered temporary since shareholders can always liquidate the firm rather than suffer from indefinite losses. Because of this liquidation option, losses are less informative than profits about the firm’s future prospects and thus more weakly associated with return than profits.The sample consists of 643 firm-years for the period 1999-2001, available from Jakarta Stock Exchange. It is partitioned into profitable and loss firm-years in order to examines the effect of losses on the estimate regression. The statistical method used in this research is linear regression and regression correlation determination. Consistent with the evidence in Hayn (1995) the finding shows that share returns do have a lower association with losses. This result thus providing further insight into the relationship between returns and losses especially in Indonesia.